A cozinha e a mesa em Loulé medieval nos seus utensílios de uso comum: o testemunho dos Inventários de Órfãos - Iria Gonçalves (Medievalista)
The documents of the so-called Fund of the judge of the orphans of Loulé, from the Historical Archive of this city, are rare pieces in the Portuguese medieval context, with enormous interest for the study of medieval orphanage. Although produced to safeguard the interest of the orphans, and to follow the way the respective guardians administered their property or held accounts of these tutelages, they equally reveal many other facets of medieval living. Ten of them, drafted over seventy years, between 1408 and 1479, are used here to recover the utensils used in the kitchen and at the medieval table, associated with the storage, cooking and consumption of food. Not forgetting the nature and limits of the written records, but combining their reports with archaeological and ethnographical data, a fairly coherent picture was obtained, with observations on the social significance of the shortage of equipments in certain households, or on the distinction denounced by the quality and rarity of some other kitchenware.